2016
DOI: 10.1371/journal.pone.0168108
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Power Density and the Degree of Nonlinearity in Intrinsic Components of Anesthesia EEG by the Hilbert-Huang Transform: An Example Using Ketamine and Alfentanil

Abstract: Empirical mode decomposition (EMD) is an adaptive filter bank for processing nonlinear and non-stationary signals, such as electroencephalographic (EEG) signals. EMD works well to decompose a time series into a set of intrinsic mode functions with specific frequency bands. An IMF therefore represents an intrinsic component on its correspondingly intrinsic frequency band. The word of ‘intrinsic’ means the frequency is totally adaptive to the nature of a signal. In this study, power density and nonlinearity are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Understanding the association between HFRS incidence and climate change (using MEI as a proxy, measuring coupled oceanic-atmospheric character of ENSO event) provides a potential auxiliary way to assess the public health effects of global climate change, since climate variability has important effects on wildlife population dynamics [64,65]. The Hilbert-Huang transformation is a powerful tool for solving mode-mixing problems and can be also used as a filter for decomposing raw HFRS incidence series into several independent series with disparate modes, i.e., IMFs [66]. Different component series were obtained that describe various inherent disease characteristics that cannot be detected in the raw series.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the association between HFRS incidence and climate change (using MEI as a proxy, measuring coupled oceanic-atmospheric character of ENSO event) provides a potential auxiliary way to assess the public health effects of global climate change, since climate variability has important effects on wildlife population dynamics [64,65]. The Hilbert-Huang transformation is a powerful tool for solving mode-mixing problems and can be also used as a filter for decomposing raw HFRS incidence series into several independent series with disparate modes, i.e., IMFs [66]. Different component series were obtained that describe various inherent disease characteristics that cannot be detected in the raw series.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are the evidence of one of the limitations of the empirical mode decomposition: the so called mode-mixing, consisting in the appearance of disparate scales in an IMF, or when a signal with a similar scale appears in different IMF components. This fact has been reported and multiple procedures have been proposed to mitigate its effect (Munoz-Gutierrez et al 2018;Soler et al 2020;Tsai et al 2016;Zheng, Xu 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Some authors have recently suggested that the first IMFs decomposed from the EEG using the multivariate empirical mode decomposition could be associated to classical EEG bands (Noshadi et al 2014;Schiecke et al 2019;Soler et al 2020;Tsai et al 2016). The IMF1 would correspond to the gamma band, the IMF2 to the beta, the IMF3 to the alpha, the IMF4 to the theta, and the IMF5 and IMF6 would be sub-bands of the delta band (Tsai et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of the MEMD and the APIT-MEMD algorithms used in this study was based on software resources publicly available at the web site http://www.commsp.ee.ic.ac.uk/~mandic/research/emd.htm. For calculations in the frequency domain of EEG signals were selected the first 6 extracted IMFs, that contain the spectral range from 1 to 70 Hz as shown by other authors (Chen et al 2016;Chen et al 2017;Schiecke et al 2019;Amo et al 2017;Carella et al 2018;Zheng, Xu 2019;Zhuang et al 2017;Tsai et al 2016).…”
Section: The Other Half Of All the Uniform Projection Vectorsmentioning
confidence: 99%